POLAR OBSERVATIONS OF SOLAR COSMIC RAY EVENTS DURING THE IQSY. - Goedeke, A. D.; Masley,A. J.; Adams,G. W. (1966)
During the period of the IQSY, January 1964 through December 1965, the sun remained quiet, producing very few energetic particles. There were many instances during the IQSY when low-energy detectors on satellites and space probes registered small intensity increases. However, a few of these 'events' were associated with protons of energies exceeding 10 MeV. Moreover, the maximum intensities (of E sub p > 500 keV) were typically 1 - 8/sq cm sec ster. Most of these events were below the threshold of riometer detection. The largest solar cosmic ray event observed in 1964 by polar-based riometers was that of March 16. This event was observed by 30 and 50 Mc/s riometers at McMurdo, Antarctica, and Shepherd Bay, N.W.T., Canada. The largest event in 1965 occurred on February 5 and was the largest during the IQSY. It was associated with a class 2 flare at about 1750 UT, February 5. The propagation time between the sun and earth was about one hour. This event was well observed by satellites, space probes, and riometers. This paper discusses primarily the February 5, 1965 event. Some discussion was given to the March 16, 1964 event, other small events during the IQSY, and the recent event in March 1966. (Author) To be published in Space Research, VII, North Holland Publishing Co., Amsterdam, 1966.